2002
DOI: 10.1038/ni837
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis of Vα14i NKT cells

Abstract: CD1d-reactive natural killer T (NKT) cells with an invariant V alpha 14 rearrangement (V alpha 14i) are a distinct subset of T lymphocytes that likely have important immune-regulatory functions. Little is known regarding the factors responsible for their peripheral survival. Using alpha-galactosylceramide-containing CD1d tetramers to detect V alpha 14i NKT cells, we show here that the expansion of V alpha 14i NKT cells in lymphopenic mice was not dependent on CD1d expression and was unaffected by the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
351
6
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(387 citation statements)
references
References 52 publications
29
351
6
1
Order By: Relevance
“…Furthermore, this defect correlates with the peripheral survival data, and is consistent with the known role of IL-15 in the peripheral survival of all NKT cell subsets. Interestingly, this decrease in CD122 expression also correlates with the impaired up-regulation of NK1.1 in the Itk Ϫ/Ϫ and Itk/Rlk Ϫ/Ϫ NKT cells, and is consistent with the observation that IL-15-deficient mice have a marked decrease in mature (NK1.1 ϩ ) NKT cells, with no effect on the immature NKT cells present in the thymus (13). Putting these data together may also account for why we fail to see an increase in apoptotic/dead NKT cells in the thymus of Itk Ϫ/Ϫ and Itk/Rlk Ϫ/Ϫ mice, because these thymi contain only small numbers of mature NKT cells, with few cells reaching the stage at which they would be susceptible to an absence of IL-15.…”
Section: Tec Family Kinase-deficient Nkt Cells Show Impaired Survivalsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, this defect correlates with the peripheral survival data, and is consistent with the known role of IL-15 in the peripheral survival of all NKT cell subsets. Interestingly, this decrease in CD122 expression also correlates with the impaired up-regulation of NK1.1 in the Itk Ϫ/Ϫ and Itk/Rlk Ϫ/Ϫ NKT cells, and is consistent with the observation that IL-15-deficient mice have a marked decrease in mature (NK1.1 ϩ ) NKT cells, with no effect on the immature NKT cells present in the thymus (13). Putting these data together may also account for why we fail to see an increase in apoptotic/dead NKT cells in the thymus of Itk Ϫ/Ϫ and Itk/Rlk Ϫ/Ϫ mice, because these thymi contain only small numbers of mature NKT cells, with few cells reaching the stage at which they would be susceptible to an absence of IL-15.…”
Section: Tec Family Kinase-deficient Nkt Cells Show Impaired Survivalsupporting
confidence: 87%
“…Interestingly, the NK1.1 Ϫ NKT cells leave the thymus to populate the periphery, where they can further mature into NK1.1 ϩ NKT cells, whereas the more mature NK1.1 ϩ NKT cells generated in the thymus remain in the thymus to become a long-lived nondividing resident population (8,9,11). Furthermore, up-regulation of NK1.1 on peripheral NKT cells, which denotes their terminal differentiation, is CD1d dependent (12), whereas the survival and homeostasis of these cells depend on IL-15 (13,14).…”
mentioning
confidence: 99%
“…Similar to the case with TCR␥␦ s-IEL, enforced expression of Bcl-2 did not restore the number of NKT cells in IL-15 KO mice. As BrdU incorporation studies have shown that peripheral NKT cells are slowly dividing in an IL-15-dependent manner (46), the primary role of IL-15 in the homeostasis of these cells may be to provide proliferation signals rather than survival signals.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, lack of homeostatic proliferation in double-deficient IL-7 Ϫ/Ϫ IL-15 Ϫ/Ϫ mice, as opposed to normal expansion in single-deficient (IL-7 Ϫ/Ϫ or IL-15 Ϫ/Ϫ ) mice and in IL-7 Ϫ/Ϫ IL-15 Ϫ/Ϫ mice treated with rIL-7, suggested that ␥␦ T cell homeostatic expansion requires either IL-7 (like most ␣␤ T cells) or IL-15 (like memory CD8 ϩ ␣␤ T cells). Other examples of homeostatic proliferation inhibition among functionally different lymphocyte subsets, such as NK, NKT, and memory CD8 ϩ ␣␤ T cells have also been interpreted as reflecting overlapping cytokine requirements (13). Thus, whereas inhibition of ␥␦ T cell homeostatic expansion by ␣␤ T cells is consistent with their consumption of IL-7 and IL-15, lack of inhibition by the IL-15-dependent NK cells is likely due to the small number of NK cells, to the fact that ␥␦ T cells can use IL-7 when IL-15 is not available, or to different localization of ␥␦ and NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar approaches have been used to define the homeostatic requirements for NK cells, NKT cells, and B cells. For homeostatic expansion in lymphopenic mice, NK cells require IL-15 (12), NKT cells require IL-15 (and less IL-7) but not the Ag-presenting CD1d molecule (13), and B cells require Btk-mediated signals but not IL-7 (14).…”
Section: ␥␦ T Cell Homeostasis Is Controlled By Il-7 and Il-15mentioning
confidence: 99%